1969
DOI: 10.2337/diab.18.11.724
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism Between the Effects of Insulin and Glucagon on the Isolated Liver

Abstract: Antagonism was demonstrated between the effects of insulin and glucagon, added simultaneously to the perfusing blood, on phosphorylase activity, glucose output and urea production of the isolated rat liver. However, the degree of antagonism varied greatly, according to the action under study, and there appeared to be a clear-cut hierarchy in the effects of each hormone. For glucagon, this was (stimulation of): (1) phosphorylase activity, (2) glycogenolysis and glucose release, (3) urea production. For insulin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
1

Year Published

1974
1974
1994
1994

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(42 citation statements)
references
References 11 publications
6
35
1
Order By: Relevance
“…This observation is consistent with studies in perfused rat liver in which insulin, even when used in extremely high concentration, failed to suppress hepatic glucose release induced by supraphysiologic levels of glucagon (57). Similar observations have been made by Mackrell and Sokal who demonstrated differences in sensitivity of various hepatic processes to control by insulin and glucagon (58). It is also consistent with the observation that net glucose uptake by the canine liver does not begin until the glucagon: insulin ratio is less than 1/10 (59).…”
supporting
confidence: 80%
“…This observation is consistent with studies in perfused rat liver in which insulin, even when used in extremely high concentration, failed to suppress hepatic glucose release induced by supraphysiologic levels of glucagon (57). Similar observations have been made by Mackrell and Sokal who demonstrated differences in sensitivity of various hepatic processes to control by insulin and glucagon (58). It is also consistent with the observation that net glucose uptake by the canine liver does not begin until the glucagon: insulin ratio is less than 1/10 (59).…”
supporting
confidence: 80%
“…Studies in the isolated perfused rat liver have demonstrated antagonism between the actions of glucagon and insulin in the regulation of several metabolic processes including glycogenolysis. Several laboratories have observed that the glycogenolytic effect of physiologic levels of glucagon (3 X 10-1, 1 X 10-, 4 X 10', and 4 X 10's M) could be inhibited by insulin (5,(29)(30)(31). These same groups also noted that the glycogenolytic activity of higher doses of glucagon (6 X 10', 1 X 10 , 1 X 104, and 2 X 10' M) could not be inhibited by insulin even when extremely high insulin levels (2.5 X 10V M; 3,600 AU/ml) were employed.…”
Section: Results and Commentsmentioning
confidence: 99%
“…Furthermore, the age-associated changes in the G/I ratio determined for portal blood were almost the same as those determined for peripheral blood. While glucagon is known to increase G-6-Pase and F-1,6-DPase activities and accelerate the rate of gluconeogenesis and glucose out put in the liver, insulin suppresses the effects of glucagon (10,11,(24)(25)(26). In addition, it has been well established that the G/I ratio but not the absolute concentration of either hormone determines hepatic carbohydrate metabolism in vitro and in vivo (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%